Kemampuan Penalaran Matematis Melalui Pembelajaran Contextual Teaching and Learning (CTL) Pada Siswa SMP - Nurfadhilah Nurfadhilah; Zubaidah Amir MZ (Universitas Hamzanwadi, 2018)
The purpose of this research is to know the difference of mathematical reasoning ability between students using Contextual Teaching and Learning model (CTL) with students using direct learning model. Research type is experiment with quasi experiment research method and research design used is Posttest-Only Control Group Design. The sample technique used is purposive sampling. To see the results of the study, the data normality test, and homogeneity test using standard deviation and the mean of the sample class, then t-test to determine the difference between two classes. Based on the results of data analysis, it can be concluded that: There are differences in students' mathematical reasoning ability to learn using Contextual Teaching and Learning (CTL) learning model with students who learn to use direct learning with an average experimental class of 93,75 higher than the control class of 81,90.